Stable long-term operation of an upflow anammox sludge bed reactor at mainstream conditions. (1st January 2018) - Reino, Clara; Suárez-Ojeda, María Eugenia; Pérez, Julio; Carrera, Julián
Abstract: The efforts for implementing the anammox process at mainstream conditions with high nitrogen removal rates have gained much attention in the race for achieving an energy-positive urban wastewater treatment plant. Here, the successful and stable long-term operation of an Upflow Anammox Sludge Bed (UAnSB) reactor treating a low-strength synthetic influent amended with ammonium and nitrite for 420 days, and a nitrite-amended pre-treated real urban wastewater for 110 days at temperatures as low as 11 °C is presented. The short and long-term effects of temperature on anammox activity were assessed when the synthetic influent was treated, and the UAnSB reactor was demonstrated to be a robust reactor to confront low temperatures, typically found at mainstream conditions. In fact, a nitrogen loading rate as high as 1.8 ± 0.1 g N L −1 d −1 with 82 ± 4% of nitrogen removal was achieved at 11 °C treating the low-strength synthetic influent. Furthermore, the effect of treating a nitrite-amended pre-treated real urban wastewater at 11 °C at long-term in the UAnSB reactor was evaluated, and a stable operation was achieved with a high average nitrogen removal rate (1.2 ± 0.5 g N L −1 d −1 ). The relative abundance of anammox bacteria was maintained higher than 70% according to fluorescence in situ hybridization during the whole operation, being Candidatus Brocadia anammoxidans the predominant microbial species. The presence of heterotrophs in the sludge bed was surmised through heterotrophic batch tests, but anammox activity was demonstrated to be higher than heterotrophic activity, even when the synthetic influent was replaced by the nitrite-amended pre-treated real wastewater. The feasibility of operating an enriched anammox reactor at high nitrogen removal rate at long-term at mainstream conditions was demonstrated in this study. Graphical abstract: Image 1 Highlights: High anammox activity was reached in an UASB reactor with urban wastewater at 11 °C. The UASB anammox reactor maintained its activity during temperature disturbances. The overcapacity developed in the UASB reactor helped to face adverse conditions.